Blood donors deferral prevalence and causes in a tertiary health care hospital, southern Nigeria - Henshaw Uchechi Okoroiwu; Enosakhare Aiyudubie Asemota (BMC, 2019)
Abstract Background Blood transfusion is a life-saving intervention. However, the safety of the donor and the recipient is paramount. This study was aimed at determining the blood donation deferral pattern of University of Calabar Teaching Hospital. Methods A retrospective analysis of the prospective donors' data of University of Calabar Donor clinic within the period of March 2015 to February 2016 was conducted. Data were extracted from the donor register and analyzed. Prospective donors were screened and interviewed for causes of temporary and permanent deferrals. Result Out of the 1886 screened prospective donors, 164 (8.69%) were deferred. Though the minority of the donor population, female donors had the highest deferral rate (33.33%). There were 31.10 and 68.90% cases of temporary and permanent deferrals, respectively. Hepatitis B virus (HBV) was the highest (31.71%) cause of overall deferral as well as permanent deferral. Anemia was the major (21.95%) cause of temporary deferral as well as the second cause of overall deferrals. Commercial and replacement donors constituted 68.28 and 31.71% of the deferral cases, respectively. Conclusion HBV was found to be the overall leading cause of deferral in the studied area. This outcome poses a public health concern and should elicit measures to curb the infection rate.